2017
DOI: 10.1080/03009734.2017.1368745
|View full text |Cite
|
Sign up to set email alerts
|

Addition of exogenous sodium palmitate increases the IAPP/insulin mRNA ratio via GPR40 in human EndoC-βH1 cells

Abstract: BackgroundEnhanced IAPP production may contribute to islet amyloid formation in type 2 diabetes. The objective of this study was to determine the effects of the saturated fatty acid palmitate on IAPP levels in human β-cells.MethodsEndoC-βH1 cells and human islets were cultured in the presence of sodium palmitate. Effects on IAPP/insulin mRNA expression and secretion were determined using real-time qPCR/ELISA. Pharmacological activators and/or inhibitors and RNAi were used to determine the underlying mechanisms… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…9 D ). EndoC-βH1 cells exposed to high SP and high glucose increase their IAPP secretion without a concomitant increase in insulin secretion ( 34 ). A scenario with high levels of IAPP in the secretory pathway with a concurrent reduction of antiamyloid chaperone Bri2 could be detrimental for the cells and induce cell death.…”
Section: Resultsmentioning
confidence: 99%
“…9 D ). EndoC-βH1 cells exposed to high SP and high glucose increase their IAPP secretion without a concomitant increase in insulin secretion ( 34 ). A scenario with high levels of IAPP in the secretory pathway with a concurrent reduction of antiamyloid chaperone Bri2 could be detrimental for the cells and induce cell death.…”
Section: Resultsmentioning
confidence: 99%
“…The generation of such hybrid fusion peptides is energetically unfavorable and also requires precise joining of two proteolytic fragments in the presence of competing peptide fragments. The C-terminal fragment of 6.9HIP originates from islet amyloid polypeptide, which is present at a level of ∼1% compared with insulin (Krizhanovskii et al, 2017). It therefore appears likely that hybrid fusion peptides are produced by β cells in small quantities.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported decreased insulin content in rodent and human pancreatic beta-cells after palmitate treatment (32, 33), with evidence that the mechanism involves decreased insulin translation (33). As shown in Fig 5B, palmitate decreased insulin content in both Pex11 β knock down and control cells at high glucose, but this was less pronounced in the Pex11 β knock down cells.…”
Section: Discussionmentioning
confidence: 99%